Resenha de: Huang Hsing and the Chinese Revolution - Novais, Fernando A. (Revista de História, 1964)
CHÜN-TU-HST.YEH. — Huang Hsing and the Chinese Revolution. Stanford. Califórnia. ,Stanford University Press. 1961, 260 pp.